Story of my life [large type] - Score, Lucy (Score, Lucy. Story Lake ;, 2025)
"Hazel Hart was a successful romance novelist until a breakup drives her straight into writer's block. Having failed (and failed some more) to deliver her new manuscript, she's hiding from the world behind a wall of old takeout containers until her publisher lays down the law. If she misses her next deadline, it's The End. Desperate for inspiration, Hazel impulse-buys a historic home online and flees Manhattan to tiny Story Lake, PA. Upon her dramatic arrival involving an incident with a bald eagle she discovers the charm of her new home may have been slightly exaggerated. The house is a wreck and the town is struggling after their biggest employer shut down. Also, since her raccoon-infested home came with a seat on the town council, our introverted heroine is stuck with a front row seat to all the small-town shenanigans. But Hazel isn't worried. Not since all six feet, three inches of grouchy contractor Campbell Bishop slapped a bandage on her forehead and unintentionally inspired the heck out of her. There's only one thing to do: hire Cam and his equally gorgeous brothers to renovate her new spider museum . . . er . . . house."--